Performance and Long Term Stability of Mesoporous Silica Membranes for Desalination - Elma, Muthia (MDPI, 2013)
This work shows the preparation of silica membranes by a two-step sol-gel method using tetraethyl orthosilicate in ethanolic solution by employing nitric acid and ammonia as co-catalysts. The sols prepared in pH 6 resulted in the lowest concentration of silanol (Si–OH) species to improve hydrostability and the optimized conditions for film coating. The membrane was tested to desalinate 0.3–15 wt % synthetic sodium chloride (NaCl) solutions at a feed temperature of 22 °C followed by long term membrane performance of up to 250 h in 3.5 wt % NaCl solution. Results show that the water flux (and salt rejection) decrease with increasing salt concentration delivering an average value of 9.5 kg m(–)(2) h(–1) (99.6%) and 1.55 kg m(–)(2) h(–1) (89.2%) from the 0.3 and 15 wt % saline feed solutions, respectively. Furthermore, the permeate salt concentration was measured to be less than 600 ppm for testing conditions up to 5 wt % saline feed solutions, achieving below the recommended standard for potable water. Long term stability shows that the membrane performance in water flux was stable for up to 150 h, and slightly reduced from thereon, possibly due to the blockage of large hydrated ions in the micropore constrictions of the silica matrix. However, the integrity of the silica matrix was not affected by the long term testing as excellent salt rejection of >99% was maintained for over 250 h.